Subalternity dan unhomeliness dalam cerpen The Arrangers of Marriage karya Chimamanda Ngozi Adichie - Alaydrus, Syarifah Fairuz Shafira; Saraswati, Asri (Universitas Mulawarman, 2024)
As a black Nigerian woman who married an immigrant, Chinaza from The Arrangers of Marriage (2009) short story had to go to the United States of America and live with her husband. Being in an unfamiliar environment made her feel isolated, especially with her marriage being an arrangement in which she had no say. This research aims to reveal Chinaza’s lack of agency in gaining her voice and how it affects her alienation in a new environment. By using a qualitative descriptive method, this research applies a postcolonial approach with the help of Gayatri Spivak’s subaltern and Homi Bhabha’s unhomeliness concept. The results show that Chinaza is a subaltern who is silenced and marginalized in both her patriarchal family and her new environment in the United States. In addition, her new life in a foreign country made her feel confined between two cultures, which couldn’t seem to accept her nor was she able to accept completely. The feeling of “unhomely” that Chinaza experienced was not solely caused by living in a foreign country, but also because of her husband urging her to abandon her culture.